2003
DOI: 10.1113/jphysiol.2003.038943
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hyaluronan secretion into rabbit synovial joints in vivo by protein kinase C

Abstract: Hyaluronan (HA) is important for joint cavitation, lubrication, volume regulation and synovial fluid drainage but little is known about the regulation of joint HA synthesis/secretion in vivo. We investigated whether HA secretion into joints in vivo can be regulated by protein kinase C (PKC). Secretion into the knee joint cavity of anaesthetised rabbits was measured over 6 h by washout and chromatography. Joints received intra‐articular injections of Ringer vehicle (control) or an activator of classical PKC iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
4

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 47 publications
4
31
0
4
Order By: Relevance
“…Previous studies have shown that TNF-␣ activates PKC (62) and that PKC activation promotes HA synthesis by HAS (63). We now show that TNF-␣ stimulation promotes association of HA with CD44 at the cell periphery and that this association is accompanied by the interaction of CD44 with pERM, in particular with phosphorylated moesin.…”
Section: Tnf-␣ Promotes the Formation Of Ha⅐cd44⅐permmentioning
confidence: 49%
“…Previous studies have shown that TNF-␣ activates PKC (62) and that PKC activation promotes HA synthesis by HAS (63). We now show that TNF-␣ stimulation promotes association of HA with CD44 at the cell periphery and that this association is accompanied by the interaction of CD44 with pERM, in particular with phosphorylated moesin.…”
Section: Tnf-␣ Promotes the Formation Of Ha⅐cd44⅐permmentioning
confidence: 49%
“…HA secretion is also stimulated by synovial mechanical distortion per se, as shown using sterile, non-pyrogenic infusions into un-inflamed joints (Coleman et al, 1997). Little is known, however, about the signal transduction pathway(s) mediating this response (Anggiansah et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The presence of a latent form of endogenous HAS was suggested by experiments showing that protein kinase C activation stimulates hyaluronan synthesis partly through mechanisms independent of protein synthesis (30,31). Regulated mobilization of HAS from the Golgi complex would provide cells a way of responding to challenges that require rapid activation of hyaluronan synthesis.…”
Section: C-terminal Truncation Of Has3 and Exit From Er-mentioning
confidence: 99%